Roland Barthes’ Semiotic Analysis of the MBG (Free Nutritious Meal) Issue on @Tempodotco Instagram Account - Jaelani, Hilmi; Nurfalah, Farida; Hermawan, Abdul Jalil (Indonesian Journal of Advanced Research, 2025)
Currently, the use of social media is increasing, with Instagram being popular in Indonesia. In October 2023, there were 104.8 million Instagram users in Indonesia. The Free Nutritious Meal (MBG) program launched by the government aims to provide healthy food for vulnerable groups, especially children. This study aims to analyze the meaning of posts related to the Free Nutritious Meal issue on Instagram using Roland Barthes' semiotic theory. This study is qualitative descriptive, describing and analyzing the meaning of Instagram posts about the MBG program. This method focuses on the interpretation of visual and textual signs, and their influence on public understanding. This study shows that visual and text posts on the Instagram account @tempodotco related to the Free Nutritious Meal (MBG) program not only function as information media, but also form deeper meanings through visual and narrative signs. By using Roland Barthes' semiotic analysis, namely through three levels of significance: denotation, connotation, and myth, it was found that the MBG discourse strategically presents the state as the main actor that is "present", "cares", and "saves" the people from the nutritional crisis.